Cosmic-ray-induced correlated errors in superconducting qubit array - Xuegang Li; Junhua Wang; Yao-Yao Jiang; Guang-Ming Xue; Xiaoxia Cai; Jun Zhou; Ming Gong; Zhao-Feng Liu; Shuang-Yu Zheng; Deng-Ke Ma; Mo Chen; Wei-Jie Sun; et al. (Nature Communications)
Abstract Correlated errors may devastate quantum error corrections that are necessary for the realization of fault-tolerant quantum computation. Recent experiments with superconducting qubits indicate that they can arise from quasiparticle (QP) bursts induced by cosmic-ray muons and γ-rays. Here, we use charge-parity jump and bit flip for monitoring QP bursts and two muon detectors in the dilution refrigerator for detecting muon events. We directly observe QP bursts leading to correlated errors that are induced solely by muons and separate the contributions of muons and γ-rays. We further investigate the dynamical process of QP burst and the impact of QP trapping on correlated errors and particle detection. The proposed method, which monitors multiqubit simultaneous charge-parity jumps, has high sensitivity to QP bursts and may find applications for the detection of cosmic-ray particles, low-mass dark matter, and far-infrared photons.